Analisis Jabatan dalam Meningkatkan Efektivitas Kinerja Guru - Guitari Dwi Rengganis; Maghfiratut Debby; Maritsa Hariyanti; M. Alif Yusro; Mu’alimin Mu’alimin (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Job analysis is a strategic tool in improving teacher performance, which serves to identify the tasks, responsibilities, and obligations inherent in the position. The main issue raised is the importance of placing teachers according to their qualifications and skills. Research shows that proper placement can improve teaching effectiveness and student learning outcomes, because teachers who understand their roles can make better contributions to the educational process. Related studies show that job analysis not only helps in teacher placement, but also in their professional development. By identifying training needs, schools can design appropriate programs to improve teacher competency. Previous research has indicated a positive relationship between job analysis and teacher performance, but there is still a lack of understanding of the specific factors that influence the effectiveness of job analysis itself. Existing research gaps include the lack of exploration of how job analysis can be implemented effectively in different contexts and its impact on teacher motivation and commitment. Although there is evidence that job analysis has a positive effect on performance, further research is needed to explore other variables that may contribute to the success of this implementation. Therefore, this study aims to provide further insight into the application of job analysis as a strategy to improve teacher performance in schools.